Marketing plans : how to prepare them, how to use them - McDonald, Malcolm; Wilson, Hugh, 1962- (Hoboken, N.J. : Wiley, 2011)
'Marketing Plans, Seventh Edition presents a practical, no-nonsense style and approach that helps and encourages practicing managers with the difficult task of marketing planning. This helpful text illustrates the process of preparing a marketing plan, how to manage that process, and how to put the plan in action. The new edition has been thoroughly updated with contemporary thinking and includes new information on multi-channel integration and other new electronic routes to market. All case material and examples have also been revised.'--
'This book is THE market leader on the topic. Now heading into its 7e its popularity speaks for itself - USP: The book is a rigorous step-by-step guide on how to do marketing planning. The step-by-step approach is taken within each chapter, and from chapter to chapter. - The book includes application questions, exercises at the end of every chapter, and mini-case studies. - An online student resource is available as an accompaniment to the book. - Detailed guidelines on how to implement all the concepts and methodologies outlined in the book to literally handhold the reader throughout the process'--
Includes bibliographical references and index.
Keywords: Marketing -- Management; Marketing -- Planning